Novel haemodynamic structures in the human glomerulus - Neal, C.R.; Arkill, K.P.; Bell, J.S.; Betteridge, K.B.; Bates, D.O.; Winlove, C.P.; Salmon, A.H.J.; Harper, S.J. (American Physiological Society, 2018)
To investigate human glomerular structure under conditions of physiological perfusion we have analysed fresh and perfusion fixed normal human glomeruli at physiological hydrostatic and oncotic pressures using serial resin section reconstruction, confocal, multiphoton and electron microscope imaging. Afferent and efferent arterioles (21.5±1.2µm and 15.9±1.2µm diameter), recognised from vascular origins, lead into previously undescribed wider regions (43.2±2.8 µm and 38.4±4.9 µm diameter) we have termed vascular chambers (VCs) embedded in the mesangium of the vascular pole. Afferent VC(AVC) volume was 1.6 fold greater than Efferent VC(EVC) volume. From the AVC long non-branching high capacity conduit vessels (n=7) (Con; 15.9±0.7µm diameter) led to the glomerular edge where branching was more frequent. Conduit vessels have fewer podocytes than filtration capillaries. VCs were confirmed in fixed and unfixed specimens with a layer of banded collagen identified in AVC walls by multiphoton and electron microscopy. Thirteen highly branched efferent first order vessels (E1;9.9±0.4µm diam.) converge on the EVC draining into the efferent arteriole (15.9±1.2µm diam.). Banded collagen was scarce around EVC. This previously undescribed branching topology does not conform to the branching of minimum energy expenditure (Murray’s law), suggesting even distribution of pressure/flow to the filtration capillaries is more important than maintaining the minimum work required for blood flow. We propose that AVCs act as plenum manifolds possibly aided by vortical flow in distributing and balancing blood flow/pressure to conduit vessels supplying glomerular lobules. These major adaptations to glomerular capillary structure could regulate haemodynamic pressure and flow in human glomerular capillaries.